Effect of adding epoxy groups to poly (butyl acrylate) on electro- viscoelastic response: Insight from molecular dynamics simulation. (10th April 2020) - Qin, Han; Ning, Nanying; Tian, Ming; Zhang, Liqun; Mi, Jianguo
Abstract: Using the all-atom molecular dynamics simulations integrated with the time−temperature superposition principle, we have probed the dielectric modification of poly (butyl acrylate), for example, to understand the effect of added polar groups on the dielectric and viscoelastic properties of poly (butyl acrylate-co-glycidyl methacrylate). We have verified that, after addition of 22% glycidyl methacrylate to formulate the copolymer, its dielectric permittivity can be improved about 50%, whereas the corresponding dielectric loss has been not significantly raised at low frequency. On the other hand, according to the hysteresis losses of tension–recovery and compression–recovery processes, the permanent deformation of poly (butyl acrylate) has also been diminished. Due to the significant increase of modulus, the actuated strain drops about 20%. As a consequence, the effective simulation method is capable of quantitatively evaluating the contribution of polar groups to the electro-mechanical coupling of dielectric elastomers. Graphical abstract: Image 1 Highlights: Electro-mechanical coupling of PBA was quantitatively evaluated by MD simulation. The dielectric strength of PBA can be enhanced 50% by adding polar epoxy groups. The enhancement mechanism was interpreted by orientation polarization of dipoles. The corresponding dielectric loss was not significantly improved at low frequency. The deformation of PBA can be diminished by adding a certain amount of GMA.